Relationship between Mathematics Anxiety and Academic Achievement among Secondary School Students: A Comparative Study of Gender and School Type - Jyoti Kalwani; Lubhawani Tripathi (International Journal of Scientific Research in Humanities and Social Sciences, 2025)
Mathematics anxiety has been widely recognized as a psychological barrier affecting students’ learning, problem-solving, and performance in school. This study investigates the relationship between mathematics anxiety and academic achievement among secondary school students. A sample of 600 students (300 boys and 300 girls) was drawn from government and private schools through stratified random sampling. Data were collected using a standardized Mathematics Anxiety Scale and mathematics achievement scores obtained from school records. Statistical analysis using Pearson’s correlation coefficient revealed a significant negative relationship between mathematics anxiety and academic achievement. Findings suggest that higher levels of mathematics anxiety are associated with lower academic performance, with gender differences observed in levels of anxiety but not in the overall direction of the relationship. The study emphasizes the need for school-based interventions, anxiety-reduction strategies, and supportive teaching methods to improve both students’ emotional well-being and academic outcomes.